THE INHIBITION OF RED CHILIES RIPENING PROCESS AT FRESH WEIGHT AND TOTAL CARBOHYDRATE CONTENT BY RED LIGHT - Martha Lulus Lande; Salman Farisi (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
The research was conducted in a factorial experiment with factor A: far-red light treatment with 2 levels: control (without far-red light), and treatment (far-red light). Factor B was a time of observation with 3 levels: 4, 6, 8 days after wrapping. Wrapping each detached fruit in a combination of four layers of blue-colored plastic, one layer of green-colored plastic, and two layers of red-colored plastic resulted in a red light treatment. Transmission measurement of that plastic combined with a spectrophotometer at wavelength 700-735 nm was 75%. To deter fresh weight, each fruit was weighted with an analytical balance. Total soluble carbohydrate content was determined by the phenol-sulfuric method and counted based on the glucose standard curve (mg/gram tissue). Analysis of variance was conducted at a 5% significant level, and if the interaction was significant, then continued with simple effect determination at a 5% significant level by the F test. The fresh weight average of the soluble carbohydrate content of treated fruits was higher than the control. The fresh weight of chili fruits was relatively constant during observation of both treated and controlled fruits. The total soluble carbohydrate content average relatively did not differ between treated and control fruits. Total soluble carbohydrate content was increased 6 days after treatment and decreased 8 days after treatment. The result of this research concluded that red light inhibited the ripening process of chili fruits by slowing the decrease of fresh weight.